Resilient manufacturing: case studies in Thai automotive industries during the COVID-19 pandemic - Kaeo-Tad Najavadh (Sciendo, 2021)
The coronavirus pandemic is a crisis that disrupts the global supply chain and slows down the world economy. A significant challenge for the companies in the manufacturing sector is to mitigate risks related to the COVID-19 outbreak. Grounded in the resilience theory, resilience (i.e., prepare, prevent, protect, respond, and recover processes) aims to manage risks and ensure business continuity. This research aims to identify the key factors for the resilient manufacturing management of Thai automotive industries during the COVID-19 outbreak. Three outstanding companies of tier 1 automotive suppliers have been selected as case studies in this work. This qualitative research was completed by using a semi-structured interview. The target interviewers were CEOs or general managers. The data analysis was divided into two phases. Phase one summarised the interview data of each company. Phase two used thematic analysis and cross-case analysis to identify resilience practices’ patterns, themes, and multi-factors. The findings indicate three key factors to enhance resilience: leadership, technology, and the firm’s experience in handling emerging events. Together, these factors help enterprises to prepare for Business Continuity Planning (BCP), improve supply chain management, and increase the firm’s ability to recover from disruption situations. This paper contributes to the literature on the supply chain resilience in the automotive industry by providing a guideline for firms to implement resilience practices, improve business operations, and increase firm’s capabilities, both as human skills and technologies, to deal with a novel crisis. Resilience practices response to the COVID-19 outbreak not only helps the companies minimise business disruption in the short-term but also includes the long-term response strategies for unknown events. For this purpose, the case study research was conducted to investigate the resilience strategies during the COVID-19 pandemic and determine the critical success factors of resilience implementation in the Thai automotive industry.